Histopathologic and immunophenotypic profile of a spontaneous mammary carcinoma in a male Humboldt's white‐fronted capuchin (Cebus albifrons). Issue 1 (12th November 2021) - Carvalho, Thaynara Parente de; Oliveira, Ayisa Rodrigues de; Santos, Daniel Oliveira dos; Cassali, Geovanni Dantas; Garcia, Ana Paula Vargas; Pereira, Fernanda Mara Aragão Macedo; Soares‐Neto, Lauro Leite; Silva, Monique Ferreira; Paixão, Tatiane Alves; Santos, Renato Lima
Abstract: A 20‐year‐old male captive Humboldt's white‐fronted capuchin ( Cebus albifrons ) that died accidentally had a small non‐ulcerative mammary nodule diagnosed as a mammary carcinoma. Immunohistochemistry demonstrated that neoplastic cells were positive for pan‐cytokeratin and cytokeratin‐7. Approximately 20% of neoplastic cells were positive for Ki‐67. Neoplastic cells expressed estrogen and progesterone receptors.